A Study of Subtitle Translation of English Taboo Words into Thai in Adult Animated Series entitled Big Mouth: การศึกษาการแปลถ้อยคำต้องห้ามในบทบรรยายใต้ภาพชุดการ์ตูนแอนิเมชันสำหรับผู้ใหญ่ เรื่อง Big Mouth จากภาษาอังกฤษเป็นภาษาไทย - เถาวัลย์ ชนัญชิดา (JOURNAL OF LANGUAGE, RELIGION AND CULTURE, 2021)
The objectives of this paper are to study translation strategies of taboo words by using translation strategies proposed by Baker (2018) as a framework and to study the frequency of each strategy. Taboo word translations are collected from Thai subtitles of adult animated series entitled Big Mouth including season 1, 2, and 3 since it represents taboos such as sex, diseases, and addressing, leading to frequent occurrences of taboo words in the characters’ conversations. The results reveal that there are eight translation strategies: using cultural substitution (26.88%), using a more neutral/less expressive word (26.07%), literal translation (16.35%), using a more general word (12.41%), omitting words (8.65%), paraphrasing with unrelated words (5.83%), paraphrasing with related words (3.51%), and using a loan word or loan word plus explanation (0.31%). Using cultural substitution is the most common translation strategy, followed by using a more neutral/less expressive word. Using a loan word or loan word plus explanation is the least frequent method.